’’ارمغان حجاز‘‘ اور’’ ارمغانِ پاک‘‘ میں تاریخی شعور کے اشتراکات:تجزیاتی مطالعہ: Commonalities of historical consciousness in “Armaghan-e Hijaz and Armaghan-e-Pak - اختر, یاسمین; بتول, ڈاکٹر سائرہ (Tashkeel e Jadeed, 2024)
Allama Iqbal is the intellectual leader of the Muslims of Subcontinent. Armaghan-e-Hijaz is his last book published in 1938. This book is an extract of his thought and philosophy. It has some allegorical poems which have the objective to awaken consciousness of the Muslims of Sub-continent and the Muslims of World. He is the convince of thought and practical, teaches freedom and dislikes slavery “Armaghan-e-Pak” is a long poem of Aslam Ansari which contains the two millenniums of past and present of Muslim of Sub-continent, it also has bright possibilities of future Chief attribute of both the books is that they convey the message of hope and practicality instead of disappointment or hopelessness. In this research article the analysis of Iqbal and Aslam Anasari’s contribution of historical consciousness will be done in reference to these two books.